Identity threat and stigma in cancer patients. Issue 1 (25th September 2014) - Knapp, Sarah; Marziliano, Allison; Moyer, Anne
Cancer stigma has undergone an important transformation in recent decades. In general, this disease no longer fits squarely into Goffman's classic taxonomy of stigmatized conditions. This review will demonstrate that, with important adaptations, an identity-threat model of stigma can be used to organize cancer stigma research post-Goffman. This adapted model postulates that one's personal attributions, responses to situational threat, and disease/treatment characteristics can be used to predict identity threat and well-being of individuals with cancer. Implications for further research and clinical practice are discussed.